2019
DOI: 10.1177/2631774519853160
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of digital cholangioscopy in management of indeterminate biliary strictures and complex biliary stones: a single-center study

Abstract: Aims: Endoscopic management of indeterminate strictures and complex stones remains a challenge, for which the latest generation single-operator digital cholangioscope (SpyGlass DS) has shown promising results. We aimed to study the clinical impact of single-operator digital cholangioscope at our tertiary academic center. Methods: We retrospectively reviewed all digital cholangioscopies performed from June 2015 to May 2018. Patient characteristics, procedure characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Furthermore, 132 articles were excluded, because these did not report the diagnostic accuracy of DSOC by SpyBite in the diagnosis of IDBS. The remaining 54 studies were evaluated, and a total of 11 studies [10][11][12][13][14][15][16][17][18][19][20] that satisfied the selection criteria, which involved 323 patients for SpyBite biopsy (SB), were included in the present meta-analysis ( Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 132 articles were excluded, because these did not report the diagnostic accuracy of DSOC by SpyBite in the diagnosis of IDBS. The remaining 54 studies were evaluated, and a total of 11 studies [10][11][12][13][14][15][16][17][18][19][20] that satisfied the selection criteria, which involved 323 patients for SpyBite biopsy (SB), were included in the present meta-analysis ( Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…Four studies were from the United States [11,12,16,18], five studies were from Europe [10,[13][14][15]20], one study was from Asia [17], and one study was from multiple continents [19]. Furthermore, five studies were prospective studies [11,16,17,19,20], two studies were prospective randomized trials [11,19], and six studies were retrospective studies [10,[12][13][14][15]18]. In addition, four studies were multicenter trials [15,16,18,19].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The challenge is the diagnosis of the indeterminate biliary stricture and the management of difficult bile stones endoscopically. The recent standard of care for the evaluation of the biliary stones is seen on MRCP, CT, or ultrasound beginning with ERCP, this technique utilizes fluoroscopy for the creation of 2D images for the localization and characterization of the bile duct pathology extent [5], [6].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the benefit of using SOC in patients with both difficult and missed bile duct stones ( Figure 1). Stones can be classified as difficult when they are larger in size (>15 mm), impacted, located in a difficult locations such as near strictures, or if there are multiple stones present [9]. Various locations in the bile duct network have also been described where stones may be hidden or missed from detection using magnetic resonance cholangiopancreatography (MRCP) and ERCP [10].…”
Section: Biliary Stonesmentioning
confidence: 99%